Efficient Catalyst for Both Suzuki and Heck Cross‐Coupling Reactions: Synthesis and Catalytic Behaviour of Geometry‐ Constrained Iminopyridylpalladium Chlorides. Issue 16 (2nd August 2016) - Tang, Yujie; Zeng, Yanning; Hu, Qingxia; Huang, Fang; Jin, Liqun; Mo, Weimin; Sun, Nan; Hu, Baoxiang; Shen, Zhenlu; Hu, Xinquan; Sun, Wen‐Hua
Abstract: A series of geometry‐constrained iminopyridyl‐palladium chlorides were synthesized and characterized. These phosphine‐free palladium complexes were explored for their catalytic activities in both Suzuki and Heck cross‐coupling reactions, achieving turnover numbers as high as 10 6 towards various aryl bromides, even those containing various functionalities. In addition, the influence of substituents with steric and electronic factors was reflected by the differences observed in their activities. Abstract :